Public Private Partnership in Transmission Systems Model Transmission Agreement - Planning Commission (Planning Commission, 2014)
The mid-term review of the Eleventh Five Year Plan suggests that the investment in infrastructure will be about 8.4 per cent of GDP in the terminal year of the Eleventh Plan (2011-12). This is a significant improvement over an investment level of 5.7 per cent of GDP during the last year of the Tenth Plan (2006-07). However, a further ramp up in the pace of investment would be necessary in order to reach an aggregate of about 10 per cent of GDP during the Twelfth Plan period with a view to sustaining a 9 per cent growth in GDP.
Planning Commission Government Of India
Planning Commission Government of India